Agility Index as a Measurement Tool Based on Stimuli Number and Traveling Distances. Issue 8 (August 2017) - Zemková, Erika
Abstract : Abstract: Zemková, E. Agility Index as a measurement tool based on stimuli number and traveling distances. J Strength Cond Res 31(8): 2141–2146, 2017—The purpose of this study was to develop an Agility Index (AI), plus related methodology, for representing and quantifying the data variability of agility performance, incorporating varied stimuli number and traveling distances. A group of 84 physically fit subjects performed the agility test. Their task was to touch, with either the left or the right foot, 1 of 4 mats according to the location of a stimulus in one of the corners of the screen. Results showed no significant changes in agility time during 60 responses, when subjects traveled a distance of 0.4 m (6.3%, p = 0.326). However, agility time increased significantly after 40 responses when traveling 0.8 m (12.5%, p = 0.044), after 20 responses when traveling 1.6 m (18.6%, p = 0.028), and after 10 responses when traveling 3.2 m (18.3%, p = 0.029). To estimate the contribution of movement time to the agility time, the AI was proposed. This was defined as a ratio of reaction time and agility time, divided by the previously determined coefficient for each distance traveled. No significant differences between the 2 test occasions in the AI and the ICC values in range from 0.88 to 0.93 and SEM from 7.6 to 8.8% signify that it is of sufficient stability and reliability to be used in practice. The AI is crucial for the sport-specific assessment of agility performance that differs in the number of stimuli and traveling distances. Also, it can be useful for comparing individuals with varied performance levels and the evaluation of agility training efficiency.